Effects of using phase change material and non-Newtonian power law nanofluid on different sides of a double pipe heat exchanger for phase change dynamics and energy performance improvements - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Wiley, 2022)
In this study, the effects of using phase change material (PCM) and non-Newtonian power law (PL) fluid on the performance features of a double pipe heat exchanger were numerically assessed with finite element technique. PCM and PL fluid were used in different sides of the heat exchanger while impacts of cold side fluid Re number, nanoparticles loading amount, and PL index of fluid on the dynamics characteristics of phase change process, and thermal performance were examined. There is a reduction of 71.5% in the full phase transition time (td) when cases with Re = 100 and Re = 300 are compared while cold fluid exit temperature rises by about 5.8 K with PCM-installed heat exchanger as compared to non-PCM configuration at Re = 300. As cases with different PL indices (n) between n = 0.8 and n = 1.2 are compared, the value of td rises by about 34%. For different nanoparticle loading, variation of td depends upon the PL index and its value rises with higher n at the highest solid volume fraction. The particle size has also impacts on the variation of td and exit temperatures which is more pronounced for power n values. A polynomial regression model is used for the estimation of td.
Keywords: energy storage; finite element method; heat exchanger; nanofluids; non-Newtonian; phase change process; polynomial regression